2017
DOI: 10.1016/j.jclepro.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Exergy analysis of a hydrogen and water production process by a solar-driven transcritical CO 2 power cycle with Stirling engine

Abstract:  A novel cogeneration plant including Stirling engine to produce water and hydrogen. A dynamic RO model including recovery turbine for different permeate flow rate. About 8% reduction in exergy destruction in the system using ideal Stirling engine. More electrical power production, higher than both LNG and CO 2 power cycle. Electrolyzer-based ZLD approach by employing electrolyzer beside RO desalination. ACCEPTED MANUSCRIPT AbstractThis study attempts to go beyond the conventional framework of the integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(46 citation statements)
references
References 39 publications
2
44
0
Order By: Relevance
“…In another study, they modified the system by replacing the condenser with a Stirling engine. 29 Similar to this study, Ahmadi et al 23 carried out a thermodynamic analysis of solar-powered tCO 2 -RC integrated with thermal energy storage tank and LNG system. Flat plate collectors were proposed for solar heat recovery.…”
mentioning
confidence: 87%
“…In another study, they modified the system by replacing the condenser with a Stirling engine. 29 Similar to this study, Ahmadi et al 23 carried out a thermodynamic analysis of solar-powered tCO 2 -RC integrated with thermal energy storage tank and LNG system. Flat plate collectors were proposed for solar heat recovery.…”
mentioning
confidence: 87%
“…In a study, Rankine cycle working with ammonia‐water was compared to regenerative Rankine power generation cycle by applying second law of thermodynamics and exergy analysis . Exergy topological approach was applied in an organic Rankine cycle and in micro‐organic Rankine heat engines in order to represent an approximation of the exergy destruction by utilizing various working fluid . They carried out their research on the simulation and exergy analysis of a 600 MWe and 800 MWe Oxy combustion pulverized coal‐fired power plant.…”
Section: Three‐e Analyses Of Power Plantsmentioning
confidence: 99%
“…79 Exergy topological approach was applied in an organic Rankine cycle and in micro-organic Rankine heat engines in order to represent an approximation of the exergy destruction by utilizing various working fluid. 11,[80][81][82][83][84][85][86] They carried out their research on the simulation and exergy analysis of a 600 MWe and 800 MWe Oxy combustion pulverized coal-fired power plant. Blanco-Marigorta et al 87 identified the location, magnitude and the thermodynamic reasons for inefficiencies in a solar thermal power plant using exergy analysis.…”
Section: Literaturementioning
confidence: 99%
“…Solar energy is one of the most popular renewable energies which is evolving noticeably in recent years due to its availability and ease of exploitation . Solar energy are applied for different purposes such as heating, desalination and electricity generation as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Annual growth rate of renewable energies for the world between 1990 and 2014 was 2.2% which had higher rate than total primary energy supply (1.9%). 10 Solar energy is one of the most popular renewable energies [11][12][13] which is evolving noticeably in recent years due to its availability and ease of exploitation. [14][15][16] Solar energy are applied for different purposes such as heating, 17 desalination 18 and electricity generation as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%